Alterations in opioid inhibition cause widespread nociception but do not affect anxiety-like behavior in oral cancer mice - Ye, Yi (2017)
Widespread pain and anxiety are commonly reported in cancer patients. We hypothesize that cancer is accompanied by attenuation of endogenous opioid-mediated inhibition, which subsequently causes widespread pain and anxiety. To test this hypothesis we used a mouse model of oral squamous cell carcinoma (SCC) in the tongue. We found that mice with tongue SCC exhibited widespread nociceptive behaviors in addition to behaviors associated with local nociception that we reported previously. Tongue SCC mice exhibited a pattern of reduced opioid receptor expression in the spinal cord; intrathecal administration of respective mu (MOR), delta (DOR), and kappa (KOR) opioid receptor agonists reduced widespread nociception in mice, except for the fail flick assay following administration of the MOR agonist. We infer from these findings that opioid receptors contribute to widespread nociception in oral cancer mice. Despite significant nociception, mice with tongue SCC did not differ from sham mice in anxiety-like behaviors as measured by the open field assay and elevated maze. No significant differences in c-Fos staining were found in anxiety-associated brain regions in cancer relative to control mice. No correlation was found between nociceptive and anxiety-like behaviors. Moreover, opioid receptor agonists did not yield a statistically significant effect on behaviors measured in the open field and elevated maze in cancer mice. Lastly, we used an acute cancer pain model (injection of cancer supernatant into the mouse tongue) to test whether adaptation to chronic pain is responsible for the absence of greater anxiety-like behavior in cancer mice. No changes in anxiety-like behavior were observed in mice with acute cancer pain.